2013
DOI: 10.1007/s00592-013-0518-2
|View full text |Cite
|
Sign up to set email alerts
|

St. John’s wort extract and hyperforin protect rat and human pancreatic islets against cytokine toxicity

Abstract: The extract of Hypericum perforatum (St. John’s wort, SJW) and its component hyperforin (HPF) were previously shown to inhibit cytokine-induced activation of signal transducer and activator of transcription-1 and nuclear factor κB and prevent apoptosis in a cultured β-cell line. Objective of this study was to assess the protection exerted by SJW and HPF on isolated rat and human islets exposed to cytokines in vitro. Functional, ultrastructural, biomolecular and cell death evaluation studies were performed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
(44 reference statements)
1
21
1
1
Order By: Relevance
“…In vitro studies have shown that the insulin secretion is not affected when isolated β-cells from humans or rats are incubated with SJW for <24 h [37,38]. This apparent discrepancy with our results may be due either to the concomitant intake of metformin or to the fact that the human subjects took SJW for 3 weeks.…”
Section: Figurecontrasting
confidence: 99%
“…In vitro studies have shown that the insulin secretion is not affected when isolated β-cells from humans or rats are incubated with SJW for <24 h [37,38]. This apparent discrepancy with our results may be due either to the concomitant intake of metformin or to the fact that the human subjects took SJW for 3 weeks.…”
Section: Figurecontrasting
confidence: 99%
“…INS‐1E cells, simultaneously exposed to MIX and SJW (2 μg/ml) or HPF (1 μ m ) for 24 h, were collected by scraping and frozen at −80°C to be later analysed. Total RNA was extracted, purified and processed as previously described . Determinations of the relative expression levels of mRNAs were performed by real‐time quantitative RT‐PCR (RT‐qPCR), as detailed .…”
Section: Methodsmentioning
confidence: 99%
“…STAT‐1 dimers bind to specific sequence elements in the regulatory regions of numerous pro‐inflammatory and pro‐apoptotic genes and act as potent transcription factors . In previous reports, we demonstrated that an extract of the herbaceous plant Hypericum perforatum L. (St John's wort, SJW), commonly used for the treatment of mild/moderate depression, protects cultured β cells and pancreatic islets against cytokine toxicity, counteracting both STAT‐1 and NF‐κB activation, although it is more powerful against the former. By these mechanisms, SJW was able to block or reduce cytokine‐induced target gene expression, in particular iNOS, and prevent β‐cell apoptosis.…”
Section: Introductionmentioning
confidence: 97%
“…Under these evolutionary conditions, not all aspects of modern safety pharmacology can be identified and therefore the discovery of drug interference by St. John's wort extracts was a big surprise. Several case reports provided evidence for interference reactions reporting reduced cyclosporine and theophylline levels during simultaneous intake of St. John's wort extract (Ernst 1999;Breidenbach et al 2000a, b;Novelli et al 2014). The initial suspicion was confirmed by subsequent clinical studies showing that St. John's wort extract induces a decline in the concurrent therapy with immunosuppressants cyclosporine A, tacrolimus, and mycophenolic acid Mai et al 2003).…”
Section: Hyperforin As Protonophorementioning
confidence: 95%